Revitalizing the Indonesian Ulema Council’s Fatwa on the Protection of Intellectual Property Rights - Giyono, Urip; Khoirudin, Ahmad; Bahumid, Saleh Abdul Qader Ali (Al-Mustashfa: Jurnal Penelitian Hukum Ekonomi Syariah, 2025)
Intellectual Property Rights (IPR) protection in Indonesia is largely operationalized through conventional statutory instruments. Since 2005, however, the Indonesian Ulema Council (MUI) has issued Fatwa No. 1/MUNAS VII/MUI/5/2005, which frames IPR infringement as an act of ẓulm and deems it ḥarām. This article examines the fatwa’s continuing relevance within Indonesia’s contemporary IPR regulatory landscape and identifies pathways to enhance its practical effectiveness as a normative complement to state-driven protection and enforcement. The study employs doctrinal (normative-juridical) research grounded in pragmatic truth theory and deductive reasoning. Legal materials are collected through library research and analyzed qualitatively using a conceptual approach to connect Sharia-ethical reasoning with positive-law structures. The findings show that legislative reforms across key IPR regimes have created misalignments between the fatwa’s statutory references and the current legal framework, thereby weakening its legal-formal coherence. The analysis further indicates that the fatwa would be more effective if its prohibitions and categories are reformulated using nomenclature corresponding to the KUHP and/or KUHPerdata and explicitly linked to existing administrative, civil, and criminal enforcement mechanisms within Indonesia’s national legal system.Keywords: intellectual property rights; MUI fatwa; revitalization; legal nomenclature; law enforcement